Effectiveness and Safety of Lysozyme Chloride-Based Cream on Healing of Grade-Two Pressure Ulcers: A Pilot Study - Glogovac Kosanović, Milkica; Bućma, Tatjana; Prtina, Draško; Gajić, Aleksandar; Šukalo, Aziz; Mehić, Meliha; Tanović Avdić, Amna; Glamočlija, Una (Scripta Medica, 2025)
Background/Aim: Pressure ulcers develop due to prolonged periods of increased pressure on certain parts of the skin and underlying tissue. This study aimed to evaluate the efficacy and safety estimates of lysozyme-based cream in the treatment of pressure ulcers of grade two according to Yarkony-Kirk scale Methods: Adult patients with neurological diseases and severe functional deficits with grade-two pressure ulcers according to Yarkony-Kirk scale were included. All patients were treated with polarised light. Additionally, the patients were treated twice daily with a cream containing 20 mg/g of lysozyme chloride (lysozyme group) or with povidone-iodine dressings (control group). Visual checks of the ulcer were performed at the baseline and daily until the end of follow-up. Safety was evaluated by the presence of adverse reactions to treatment. Patients were followed for two months or less in case of withdrawal from the study, ulcer healing, or worsening. The Yarkony-Kirk scale grade was determined at the end of follow-up for each patient and one of the four categories was recorded: healed, improved, no changes or worsened.Results: A total of 48 subjects were included, 28 (58 %) in the lysozyme and 20 (42 %) in the control group. Age, sex, pressure ulcer position and duration of follow-up were similar between groups. The percentage of healed pressure ulcers was significantly higher in the lysozyme (71 %) compared to the control (35 %) group (p = 0.005). No adverse reactions to treatments were recorded.  Conclusion: The lysozyme-based cream was found to be effective and safe in the treatment of grade-two pressure ulcers. Additional randomised, blinded, larger studies are needed to confirm these findings.